Strategi Digital Governance dalam Meningkatkan Efisiensi Pengendalian Internal di Perkebunan Kelapa Sawit - Sinaga, Rinaldi (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2026)
This study aims to explore digital governance strategies in improving internal control efficiency in Indonesian palm oil plantations. The digital governance strategies examined include the use of the Internet of Things, blockchain, artificial intelligence, and automation to support transparency, audit efficiency, and compliance with sustainability regulations. This research employs a mixed-methods approach. Primary data were collected through questionnaires distributed to 100 respondents, semi-structured interviews with five key informants, and field observations at five plantation locations in Sumatra and Kalimantan. Quantitative data were analyzed using multiple linear regression, while qualitative data were analyzed thematically. The results show that digital governance improves internal control efficiency by reducing human errors, accelerating financial anomaly detection, strengthening supply-chain traceability, and supporting EUDR and ISPO compliance. Blockchain, artificial intelligence, and automation are identified as major drivers of post-digitalization control efficiency. However, implementation costs, limited infrastructure, weak digital literacy among smallholders, and uneven access to technology remain key barriers. The findings suggest that inclusive technology solutions, offline-sync applications, shared devices, peer-to-peer training, and government-supported digital training subsidies are needed to ensure that digital governance benefits both large plantations and smallholders.